Importance of Laparoscopy to Solve the Diagnostic Dilemma of Abdominal Tuberculosis (KYAMC Journal, 2021)
Background: Diagnosis of abdominal tuberculosis as well as histopathological confirmation is difficult because of suboptimal access to the intraperitoneal pathology. Laparoscopy provides minimally invasive access to the peritoneal cavity and materials can be collected for confirmation of diagnosis.Objectives: To study the importance of laparoscopy as a tool for the diagnosis of abdominal tuberculosis and initiation of appropriate treatment without delay.Materials & Methods: In this study 25 patients with suspected abdominal tuberculosis were selected within the period of May, 2014 to October, 2014. Diagnostic laparoscopy performed on all patients with biopsy of tissue from accessible sites.Results: Diagnostic laparoscopy with biopsy confirmed the diagnosis in 24 (96%) patients, 23 of these patients (96%) had nodules at different site of abdominal cavity and 19 of these patients (76%) had ascites. In two cases there were nodules over liver surface; biopsy was taken also from both liver nodules. One nodule revealed fibrosis and another nodule revealed tuberculosis.Conclusion: Imaging and culture of ascitic fluid may fail to confirm or exclude abdominal tuberculosis in clinically suspected cases. Laparoscopy with peritoneal tissue biopsy provided rapid and correct diagnosis of abdominal tuberculosis and should be performed early in suspected cases.KYAMC Journal.2021;12(01): 14-17